Cognitive reserve and brain volumes in pediatric acute lymphoblastic leukemia - Kesler, Shelli R. (2010)
Acute lymphoblastic leukemia (ALL) is associated with long-term, progressive cognitive deficits and white matter injury. We measured global and regional white and gray matter as well as cognitive function and examined relationships between these variables and cognitive reserve, as indicated by maternal education level, in 28 young survivors of ALL and 31 healthy controls. Results indicated significantly reduced white matter volumes and cognitive testing scores in the ALL group compared to controls. Maternal education was inversely related to both global and regional white matter and directly related to gray matter in ALL and was directly related to both gray and white matter in controls, consistent with the cognitive reserve hypothesis. Cognitive performance was associated with different brain regions in ALL compared to controls. Maternal education was significantly positively correlated with working and verbal memory in ALL as well as processing speed and verbal memory in controls, improving models of cognitive outcome over medical and/or demographic predictors. Our findings suggest that cognitive reserve may be an important factor in brain injury and cognitive outcome in ALL. Additionally, children with ALL may experience some neural reorganization related to cognitive outcome.